Nanofertilizers: A Cutting-Edge Approach to Increase Nitrogen Use Efficiency in Grasslands - Mejias, J. H.; Salazar, F.; Pérez Amaro, L.; Hube, S.; Rodriguez, M.; Alfaro, M. (Frontiers in Environmental Science, 2021)
Nitrogen (N) is the most critical element limiting agricultural production at a global scale. Despite many efforts, the N use efficiency (NUE) in agriculture remains in a range of less than 50%. Reaching targeted crop yields has resulted in N overuse, which is an economic and environmental concern worldwide. The continuous exploration of innovative solutions, has led to the synthesis of novel nanomaterials, which has unraveled a powerful tool for the development of new technological products. Nanofertilizers are one of the most promising engineered materials that are being tested, either for soil or foliar applications. Encouraging results have been obtained using nanofertilizers in different plant species, however, limited information has been reported about its use in grasslands. Commonly, N is applied to grassland soils as granular fertilizers, which may result in significant losses via surface runoff or leaching, ammonia (NH3) volatilization and N oxides (N2O, NO, NOx) emissions. Nitrogen nanofertilizers are expected to increase NUE by improving the effectiveness of N delivery to plants and reducing N losses to the environment. Information on the efficiency of the use of N nanofertilizers in grasslands species is scarce and the application strategies to avoid N losses are poorly understood. New scenarios of increasing economic and environmental constraints may represent an opportunity for N nanofertilizers application in grasslands. This article reviews its potential use as an innovative approach to improve NUE and reduce N losses to the wider environment, analyzing potential shortcomings and future considerations for animal food chains.